Bone tissue, blood lipids and inflammatory profiles in adolescent male athletes from sports contrasting in mechanical load - Agostinete, Ricardo R. [UNESP]; Duarte, João P.; Valente-Dos-Santos, João; Coelho-E-Silva, Manuel J.; Tavares, Oscar M.; Conde, Jorge M.; Fontes-Ribeiro, Carlos A.; Condello, Giancarlo; Capranica, Laura; Caires, Suziane U. [UNESP]; Fernandes, Rômulo A. [UNESP] (Public Library of Science (PLoS), 2017)
Exploring the effect of non-impact and impact sports is particular relevant to understand the interaction between skeletal muscle and bone health during growth. The current study aimed to compare total and regional bone and soft-tissue composition, in parallel to measurements of blood lipid and inflammatory profiles between adolescent athletes and non-athletes. Anthropometry, biological maturity, dual energy X-ray absorptiometry (DXA) scans, training load and lipid and inflammatory profiles were assessed in a cross-sectional sample of 53 male adolescents (20 non-athletes, 15 swimmers and 18 basketball players) aged 12-19 years. Multiple comparisons between groups were performed using analysis of variance, covariance and magnitude effects (ES-r and Cohen's d). The comparisons of controls with other groups were very large for high-sensitivity C-reactive protein (d range: 2.17-2.92). The differences between sports disciplines, regarding tissue outputs obtained from DXA scan were moderate for all variables except fat tissue (d = 0.4). It was possible to determine small differences (ES-r = 0.17) between controls and swimmers for bone area at the lower limbs (13.0%). In parallel, between swimmers and basketball players, the gradient of the differences was small (ES-r range: 0.15-0.23) for bone mineral content (24.6%), bone area (11.3%) and bone mineral density (11.1%) at the lower limbs, favoring the basketball players. These observations highlight that youth male athletes presented better blood and soft tissues profiles with respect to controls. Furthermore, sport-specific differences emerged for the lower limbs, with basketball players presenting higher bone mineral content, area and density than swimmers.